Qr code-based pop-up book: an innovative learning media for cultural diversity material in elementary schools - Trisna; Widowati, Atri; Indriyani (Jurnal Bidang Pendidikan Dasar, 2025)
Innovative learning media in primary education remains limited, affecting students’ comprehension. Cultural diversity is often taught conventionally, making it less interactive. This study develops a QR Code-based Pop-Up Book as a learning tool combining three-dimensional elements and digital technology. The Research and Development (R&D) method was applied using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Experts validated the content, media, and language, while trials were conducted with fifth-grade students at SDN 160/IV Kota Jambi. Results showed high validity scores (91% content, 89% media, 93% language), with 90% practicality and 91.8% attractiveness. The QR Code-based Pop-Up Book effectively enhances students’ understanding and has strong potential for wider use in primary education.